Stress Management and Resiliency Training in a Nurse Residency Program: Findings From Participant Focus Groups. Issue 6 (November 2019) - Chesak, Sherry S.; Morin, Karen H.; Cutshall, Susanne; Carlson, Marny; Joswiak, M. Ellen; Ridgeway, Jennifer L.; Vickers, Kristin S.; Sood, Amit
Abstract : Stress is a well-recognized phenomenon in the nursing profession, particularly for new nurses. This study (a) assessed nurse residents' experience with a stress management program and (b) informed adjustments to the program. Analysis of qualitative data revealed three themes: (a) enhanced personal and professional development, (b) sensitivity to learner needs, and (c) fostering the principles of mindfulness. A stress management program has the potential to positively enhance the new nurse's transition to work.